1989
DOI: 10.1159/000457579
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide Promotes Enteral Feeding in Preterm Infants with Feeding Intolerance

Abstract: We hypothesized that the feeding difficulties experienced by premature infants are related to immature peristaltic activity and that a bowel accelerant might promote feeding in prematures. We administered metoclopramide (Meto) to 14 infants admitted to the Intensive Care Nursery at The University of Chicago between January 1, 1984, and January 1, 1987. Each infant had failed enteral feeding on at least two separate occasions. At the time of initiation of Meto, the group of infants tolerated only 11.7 ± (SEM) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…[61][62][63] Moreover, intravenous administration of metoclopramide was more effective than placebo for enhancing gastric emptying in patients with morphine-induced gastric dysfunction, 44,64 head injury, 65 diabetic gastroparesis, 27 and preterm infants; 66 however, only two of these studies 27,44 utilized the acetaminophen absorption model to assess gastric motility.…”
Section: !mentioning
confidence: 99%
“…[61][62][63] Moreover, intravenous administration of metoclopramide was more effective than placebo for enhancing gastric emptying in patients with morphine-induced gastric dysfunction, 44,64 head injury, 65 diabetic gastroparesis, 27 and preterm infants; 66 however, only two of these studies 27,44 utilized the acetaminophen absorption model to assess gastric motility.…”
Section: !mentioning
confidence: 99%
“…In conclusion, premature infants may not benefit from routine use of cisapride to improve enteral feeding, and seem to be more vulnerable to side effects. Because other prokinetic agents have little effect on the heart, other prokinetic agents might be beneficial for improving enteral feeding in premature infants 145 …”
Section: Pediatric Diseasementioning
confidence: 99%
“…Most often gastric residuals are attributed to gut immaturity. Gastric emptying is greatly delayed in preterm infants (3); thus, drugs that may enhance gastric emptying, such as metoclopramide, have been tried in a series of cases of infants with gastric residuals, with various degrees of success (4–7). Moreover, metoclopramide is not without side effects, which include irritability, vomiting, dystonic reactions and extrapyramidal symptoms (8).…”
Section: Demographic and Outcome Variables Of The Study Infantsmentioning
confidence: 99%
“…The study by Blumenthal and Costalos included 15 infants using the serial meal technique and reported that ‘…the results indicate that metoclopramide does not promote gastric emptying in the newborn period’ (4). Another study, by Meadow et al, included 14 infants with feeding intolerance, which ‘improved steadily after metoclopramide was administered’, and which did not show any harmful side effect such as extrapyramidal symptoms, worsening of hepatic function or NEC (6). A smaller study by Sankaran et al found that metoclopramide administered to six preterm infants led to an ‘excellent response’ and withdrawal of the drug led to ‘prompt recurrence of all symptoms and signs which again disappeared on reinstitution of the medication’ (5).…”
Section: Demographic and Outcome Variables Of The Study Infantsmentioning
confidence: 99%